Do air passengers behave differently to other regional travellers?: A travel mode choice model investigation. (August 2019) - Zhou, Heng; Xia, Jianhong; Norman, Richard; Hughes, Brett; Nikolova, Gabi; Kelobonye, Keone; Du, Kai; Falkmer, Torbjorn
Abstract: This research aims to investigate travel mode choices and behaviours of air passengers and community respondents in regional Western Australia. Multinomial logit and Nested logit models were used for the mode choice analysis based on Stated-Preference survey data. The results indicate that travel cost, journey time, service frequency and seat comfort played important roles in affecting travellers' mode choices. For business trips, air passengers are willing to pay more to reduce journey time and increase seat comfort and service frequency compared to community respondents. While for non-business trips, these differences were much smaller. The findings will provide some insights in understanding people's mode choice behaviours and therefore guide policy makers and airlines in developing policies and practice. Highlights: Investigating travel mode choice and behaviour of travellers on competitive air serviced routes in regional Western Australia. Comparing travel mode choice modelling results between Multinomial logit (MNL) and Nested logit (NL) models. Investigating the differences in travel mode choice behaviour between air passengers and other regional travellers. Examining the willingness to pay (WTP) of regional travellers in Western Australia.